'-omics' technology and human reproduction: reproductomics. (September 2012) - Bellver, José; Mundi, María; Esteban, Francisco J; Mosquera, Sandra; Horcajadas, José A
The success of assisted reproduction technology is highly dependent on a precise selection of gametes and embryos and determining the best endometrial window for embryo implantation. For many years, morphological criteria have constituted the only way to assess spermatozoon, oocytes, embryos and endometrial samples in order to improve outcomes. However, this approach has reached a ceiling of success and has been related to unacceptably high rates of multiple pregnancies. New technologies have been developed in order to improve the results and reduce risks via better selection of those gametes and embryos with the highest pregnancy potential, and of more favorable endometrial environments for embryo implantation. In addition, these technologies should ideally be objective, accurate, fast and affordable. Lately, the global strategies that are being employed in reproductive medicine include genomic, transcriptomic, proteomic, metabolomic profiling of oocytes, cummulus cells, granulosa cells, embryos, endometrium and culture media. These technologies, which are included under the new term 'reproductomics', are applied at different stages of development and present unique advantages as well as limitations. The present review updates the state of the art of reproductomics in assisted reproduction, with special emphasis on potential applications, future directions and current shortcomings.